Preparation of 2-Methylnaphthalene from 1-Methylnaphthalene via Catalytic Isomerization and Crystallization - Hao Sun; Kang Sun; Jianchun Jiang; Zhenggui Gu (Bulletin of Chemical Reaction Engineering & Catalysis, 2018)
Large amounts of residual 1-methylnaphthalene are generated when 2-methylnaphthalene is extracted from alkyl naphthalene. In order to transform waste into assets, this study proposes a feasible process for preparing 2-methylnaphthalene from 1-methylnaphthalene through isomerization and crystallization. The 1-methylnaphthalene isomerization was carried out in a fixed-bed reactor over mixed acids-treated HBEA zeolite. The results showed that acidic properties of catalysts and reaction temperature were associated with the 2-methylnaphthalene selectivity, yield and catalytic stability. At a high reaction temperature of 623 K, the 2-methylnaphthalene yield was 65.84 %, and the deactivation rate was much lower. The separation of reaction products was then investigated by two consecutive crystallization processes. Under optimal conditions, the 2-methylnaphthalene purity attained 96.67 % in the product, while the yield was 87.48 % in the refining process.